STUDI IMPLEMENTASI KEBIJAKAN PERATURAN MENTERI KESEHATAN NO.97 TAHUN 2014 TENTANG PEMERIKSAAN STATUS ANEMIA CATIN WANITA DI PUSKESMAS WILAYAH KERJA KOTO TANGAH - Yessi Kartalina (HUMAN CARE JOURNAL, 2021)
Phenomenon of implementation Health Minister Rule No 97 2014 about checking anaemia for bride is to become background of this research. Unfortunately it is less to get response in low level. This research aims at analysing rule policy of it, start from (1) input, encompasses policy, man, money, material and method in checking bride anaemia in Koto Tangah community health center. (b) Process, encompasses planning, organising, actuating, controlling, recording/reporting (c) Output, to increase in term of checking anaemia status to the bride. This research uses policy analyses and it is qualitative. There are five areas as a locus. All of them are located in Koto Tangah Districts and under Koto Tangah Community Health Center. The research had conducted from October 2020 to April 2021. Rationale of locus is based on less optimum in checking anaemia for brides when they conduct general check-up in health community centre. Besides, the most of brides check their health and go to the District Religious Office in Koto Tangah than other districts. Informan in this research are purposives. They are chosen because they are seemed eligible to give information on anaemia checking to the brides. The results point out that (1) input, Padang City do not have derivative policies related to the examination of bride’s anemia status. There is no special budget for this activity. The written SOP for catin services is only available in the Air Dingin Community Health Center. The MOU with Districts Religious  Office in Koto Tangah is already exists. However, mutual commitment is still lacking. The infrastructure, which consists of Hb examination tools, reagents and Fe tablets and leaflet / form for healthy bride and groom cards, are readily available. However, the Hb examination tools at the community health centers are different. (2) The process is, there is no planning, the rule of the bride inspection officer is not there, a double standard of financing for paint inspection is found. Monitoring has never been done. (3) There is no output of anaemia status examination for puskesmas, so it cannot be analyzed because targets and achievements do not exist yet. It is recommended to the Padang City Government to make a local regulation related with Health Minister Rule No. 97 of 2014 to cross-related sectors, namely DKK Padang City, Ministry of Religion of Padang City, districts religion office (KUA) and at community health center further strengthen the input to output policy system.